Outcomes of Talar Neck Fractures: A Systematic Review and Meta-analysis. Issue 5 (May 2015) - Dodd, Andrew; Lefaivre, Kelly A.
Abstract : Objectives: To report the rates of osteonecrosis and subtalar arthritis after talar neck fractures and to examine if rates have changed over time. Data Sources: A systematic review and meta-analysis of the English literature was performed using EMBASE, MEDLINE, CENTRAL, and Cochrane in November 2011 and updated in November 2014. Study Selection: Inclusion criteria were studies examining talar neck fractures that reported talar body osteonecrosis rates as a primary or secondary outcome. Exclusion criteria included case series with <10 patients or >50% pediatric patients, inability to isolate results of talar neck fractures, primary treatment of talar excision or arthrodesis, mean follow-up of <3 months, and non-English literature. Data Extraction: Basic information was collected including journal, author, year published, level of evidence, number of fractures, and follow-up length. Specific information collected included fracture classifications, timing of interventions, method of treatment, osteonecrosis rates, subtalar arthrosis rates, and method of diagnosis of osteonecrosis. Data Synthesis: Fixed-effects models were used for meta-analysis. The overall event rate of osteonecrosis was calculated and stratified based on Hawkins classification of the talar neck fractures. Mean rates of subtalar arthritis were calculated for all studies and for studies including >2 years of follow-up. Conclusions: The overall rate of osteonecrosis was 0.312. Rates for Hawkins' types I–IV were 0.098, 0.274, 0.534, and 0.480, respectively. The mean rate of subtalar arthritis was 0.49 but increased to 0.81 in studies with >2 years of follow-up. Complication rates are high in talar neck fractures, and patients should be counseled accordingly.